1962
DOI: 10.1021/jf60119a019
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Feedstuffs, Nonprotein Nitrogen in Soybeans.

Abstract: There is an increasing interest in the development of high-protein soybeans. Since the protein content is usually measured by determining Kjeldahl nitrogen and multiplying by 6.25, the method is accurate only if the proportion of nonprotein nitrogen is small. Over 30% of the nitrogen in very immature soybeans was nonprotein nitrogen compared to 4 or 5% in mature seed. Mature soybeans were higher in nonprotein nitrogen when grown under adverse conditions. High-protein soybeans were not necessarily high in non p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

1977
1977
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…Our analysis showed that this method overestimated the net protein content by an average of 3%, due to the presence of non-protein nitrogen fractions (Figure 2 and Supplementary Table S1). This finding is consistent with previous studies that were based on a more limited number of samples (Krober and Gibbons, 1962;Thakur and Hurburgh, 2007). Relaying solely on crude protein content can be misleading when assessing soybean meal quality, especially for monogastric animals that cannot utilize non-protein nitrogen fractions.…”
Section: Discussionsupporting
confidence: 90%
“…Our analysis showed that this method overestimated the net protein content by an average of 3%, due to the presence of non-protein nitrogen fractions (Figure 2 and Supplementary Table S1). This finding is consistent with previous studies that were based on a more limited number of samples (Krober and Gibbons, 1962;Thakur and Hurburgh, 2007). Relaying solely on crude protein content can be misleading when assessing soybean meal quality, especially for monogastric animals that cannot utilize non-protein nitrogen fractions.…”
Section: Discussionsupporting
confidence: 90%
“…While in other studies there has been a good regression between these two parameters in the present study, this divergence casts some doubt on the validity of either method (Glencross et al., ). Logic suggests that the use of sum of amino acids provides a more valid assessment as it is less likely that there are non‐protein amino acids in the raw materials than non‐protein nitrogen sources (Krober & Gibbons, ). However, sum of amino acids does not account for tryptophan, albeit levels of this amino acid in most raw materials are very low and the comparison is still consistent across all samples.…”
Section: Discussionmentioning
confidence: 99%